The influence of transdermal hormone therapy on thromboembolic risk of women at menopausal period - Pertyński, Tomasz; Stachowiak, Grzegorz; Stetkiewicz, Tomasz; Faflik, Urszula (Menopause Review/Przegląd Menopauzalny, 2006)
The present article is a short review of up-to-date reports on the influence of hormone therapy (HT) on the hemostatic elements responsible for thromboembolic complications, being one of the most threatening side effect of HT administration in women at menopausal period. Transdermal HT, in a far less degree than the oral type of this therapy does it, modifies (=increases) the vascular risk of thromboembolic events. Hence it should be a therapy of the first choice for women at increased risk of thromboembolic complications in circulatory system.